The internet milieu: individualization within a globalised community - Lee, Siew Chin; Lin, Luck Kee (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2006)
Communication technologies have become deeply embedded in our lives, mediating the ways in which information is presented. Due to the global nature of this channel of communication, the world has shrunk and members of the internet may share similar cultural norms of thinking and behaving. Yet, paradoxically, the Internet is personal in that each individual has an interactive opportunity in choosing the options that can expand the breadth and depth of the information they are reading, who they interact with, and the means to achieve that interaction. These options can be expressed through a variety of media techniques. This paper is based on a study of selected websites hosted in English. It looks at language use in the Internet and illustrates the paradoxes between global and individual mediations of meaning